The Effectiveness of the Use of Bio-sand Filter and Mangrove Charcoal to Reduce Oil and Phosphate Content in the Liquid Waste Originated from the Palm Oil Company PT.PN V Sei Galuh - Dedi Budiyaka; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The liquid waste from the palm oil company is rich in phosphate and oil remains.To reduce the phosphate and oil content, a treatment such as filtering should beapplied. A study aims to understand the effectiveness of the use of bio-sand filterand mangrove charcoal to reduce oil and phosphate content in the liquid wasteoriginated from the palm oil company PT.PN V Sei Galuh, has been conductedfrom June to August 2014. The waste was flown continuously through bio-sandfilter and then flown to a processor that is filled with mangrove charcoal.Parameters measured were oil and phosphate content. The treated water was thenused to rear gold fish (Cyprinus carpio), nile tilapia (Oreochromus niloticus) andcat fish (Pangasius pangasius). The fish were reared for 30 days and the survivalrate of the fish was noted. Results shown that the use of bio-sand filter andmangrove charcoal was effective for reducing oil and phosphate content in theliquid waste of the oil palm factory. The oil content reduce, it was 34 mg/ Lbefore being treated, become 5 mg/ L after being treated with bio-sand filter andreduce into 2 mg/L after being treated with charcoal, the effectiveness was91.17%. Phosphate content was also reduce, from 6,491 mg/ L, reduce into 2,350mg/ L after being treated with bio-sand filter and charcoal (77.71% effectiveness).While the survival rate of the fish was 40% (C.carpio), 60% (O. niloticus) and77% (P. pangasius). Based on data obtained it can be concluded that the use ofbio-sand filter and mangrove charcoal processor is effective in reducing phosphateand oil content in the liquid waste originated from the palm oil industry.Keywords : liquid waste, palm oil company waste, Phosphate, Biosand filters,mangrove charcoal